Oxford textbook of anaesthesia for oral and maxillofacial surgery - Shaw, Ian; Kumar, Chandra M; Dodds, Chris (Oxford : Oxford University Press, 2010)
Includes bibliographical references and index.
This title provides a comprehensive and detailed overview of all aspects of anaesthesia for oral and maxillofacial surgery. This area represents one of the most common indications for anaesthesia worldwide and an understanding of this subject is key to the safe practice of anaesthesia.
Keywords: Anesthesia; Mouth - Surgery; Maxilla - Surgery